2001
DOI: 10.1016/s0020-7292(00)00340-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal cisplatin‐based chemotherapy vs. intravenous cisplatin‐based chemotherapy for stage III optimally cytoreduced epithelial ovarian cancer

Abstract: Intravenous and intraperitoneal chemotherapy are associated with equivalent survival in patients with minimal residual stage III epithelial ovarian cancer after optimal cytoreductive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 11 publications
0
88
0
7
Order By: Relevance
“…This resulted in a number of randomized phase III studies that demonstrated an improvement in survival for the combination of delivery of chemotherapy intraperitoneally and intravenously over chemotherapy administrated intravenously alone for select patients following primary cytoreductive surgery (Table 1). [17][18][19][20][21][22][23] GOG 172, a randomized phase III study of cisplatin administered intraperitoneally combined with both delivery of paclitaxel intraperitoneally and intravenously, published in 2006, demonstrated a 16-month improvement in median OS over intravenous administration of the same drugs alone. 18 This prompted the National Cancer Institute (NCI) to issue a rare clinical announcement regarding the clinical utility of cisplatin-based chemotherapy administered intraperitoneally in the treatment of patients with small volume (, 1 cm), advanced-stage (stage III) epithelial ovarian cancer following an attempt at maximal cytoreductive surgery.…”
Section: Intraperitoneal Chemotherapy Trials In Women With Epithelialmentioning
confidence: 99%
“…This resulted in a number of randomized phase III studies that demonstrated an improvement in survival for the combination of delivery of chemotherapy intraperitoneally and intravenously over chemotherapy administrated intravenously alone for select patients following primary cytoreductive surgery (Table 1). [17][18][19][20][21][22][23] GOG 172, a randomized phase III study of cisplatin administered intraperitoneally combined with both delivery of paclitaxel intraperitoneally and intravenously, published in 2006, demonstrated a 16-month improvement in median OS over intravenous administration of the same drugs alone. 18 This prompted the National Cancer Institute (NCI) to issue a rare clinical announcement regarding the clinical utility of cisplatin-based chemotherapy administered intraperitoneally in the treatment of patients with small volume (, 1 cm), advanced-stage (stage III) epithelial ovarian cancer following an attempt at maximal cytoreductive surgery.…”
Section: Intraperitoneal Chemotherapy Trials In Women With Epithelialmentioning
confidence: 99%
“…The basis of the experimental arms in all the randomized IP clinical trials has been IP cisplatin [5][6][7][8][9][10][11][12] . However, that agent, delivered by that route, is associated with significant toxicity, particularly neuropathy and emesis.…”
Section: Rationale For the Study Armsmentioning
confidence: 99%
“…The U.S. National Cancer Institute (nci) reviewed data from seven randomized trials comparing IV-IP with standard IV administration of chemotherapy in women who had undergone primary debulking surgery (Table i). On average, IP-IV chemotherapy was associated with a 21.6% decrease in risk of death (hazard ratio: 0.78; 95% confidence interval: 0.69 to 0.89) [5][6][7][8][9][10][11][12] . They concluded that IP-IV chemotherapy should be considered a standard of care for a select group of women with eoc.…”
mentioning
confidence: 99%
“…1,[8][9][10][11][12][13] GOG 172, the most recent GOG study, evaluated paclitaxel and cisplatin as either an IV only or as an IV/IP combination. A signifi cant benefi t in OS was identifi ed: 65.6 months in the IP arm and 49.7 months in the IV only arm (Fig 1).…”
Section: Intraperitoneal Treatmentmentioning
confidence: 99%